Demonstration of Species Composition, Stand Structure, Biomass and Carbon Storage in Stands at the Bamboo Arboretum, IPB Darmaga Campus - Bagaskara, Alamsyah; Kusmana, Cecep; Yunasfi (Journal of Tropical Silviculture, 2024)
Forest ecosystems can absorb greenhouse gases by absorbing CO2 from the air to store carbon in vegetation. The IPB Darmaga Campus Bamboo Arboretum is one of the green opn spaces on campus in an effort to reduce environmental pollution in the city. The aim of this research is to describe species composition, vegetation structure, estimate biomass potential, carbon storage and carbon dioxide (CO2) uptake, as well as describe soil properties in the Bamboo Arboretum, IPB Darmaga Campus. The method used is measuring diameter and height (trees, poles, stakes, dead wood and dead trees) as well as measuring the water content of undergrowth, seedlings, litter and twigs. Soil data collection was carried out using the purposive sampling method. The research results show that the species composition of the forest stands at the Bamboo Arboretum on the IPB Darmaga Campus is dominated by Hevea brasiliensis (rubber zone and Dipterocarpaceae zone), Bambusa blumeana (bamboo zone), and Swietenia mahagoni (mixed zone). The rubber zone is the zone with the highest value of biomass, carbon storage, and carbon dioxide uptake. The soil organic C content in the Bamboo Arboretum of the IPB Darmaga Campus in the Dipterocarpaceae zone, rubber zone and bamboo zone is high, while in the mixed zone it is medium. Keywords: Biomass, carbon, carbon dioxide, composition, necromass